About thermodynamics of Schwarzschild black holes in a three-dimensional quantum vacuum with generalized uncertainty relations - Fiscaletti Davide (Kragujevac Journal of Science)
By considering a modified version of generalized uncertainty relations in the model of a three-dimensional dynamic quantum vacuum characterized by a variable energy density, new relevant perspectives of analysis of the thermodynamics of Schwarzschild black holes are explored. The dependence of temperature and entropy of a Schwarzschild black hole with the variable quantum vacuum energy density is analyzed. Finally, the thermodynamics of Schwarzschild black holes surrounded by quintessence is studied in a picture where quintessence, and thus dark energy, is the manifestation of more elementary quantum vacuum energy density fluctuations as well as a state parameter of the vacuum.